Morning pressor surge, blood pressure variability, and arterial stiffness in essential hypertension. Issue 2 (February 2017) - Pucci, Giacomo; Battista, Francesca; Anastasio, Fabio; Schillaci, Giuseppe
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: An excess morning blood pressure surge (MBPS) may portend an increased cardiovascular risk, but the mechanisms thereof have been little investigated. The link between MBPS, short-term blood pressure (BP) variability, and arterial stiffness has not been entirely defined. Methods: In 602 consecutive untreated hypertensive patients (48 ± 12 years, 61% men, office BP 149/93 ± 17/10 mmHg), we measured carotid–femoral pulse wave velocity (cf-PWV, SphygmoCor) and 24-h ambulatory BP. Using self-reported sleep and wake times, MBPS was defined as sleep-trough (ST-MBPS), prewaking, rising. Short-term BP variability was calculated as weighted 24-h SBP SD and average real variability of 24-h SBP (ARV), that is, average of absolute differences between consecutive SBP readings. Results: ST-MBPS ( r = 0.16, P < 0.001) and rising MBPS ( r = 0.12, P = 0.003) showed a direct correlation with cf-PWV, whereas prewaking MBPS had no such relation ( r = 0.06, P = 0.14). Only ST-MBPS was independently associated with cf-PWV ( t = 1.96, P = 0.04) after adjustment for age, sex, height, office mean arterial pressure, heart rate, and renal function. This association was lost after further adjustment for weighted 24-h SBP SD ( P = 0.13) or ARV ( P = 0.24). ARV was a significant mediator of the relationship between ST-MBPS and cf-PWV ( P = 0.003). Conclusion: In untreated hypertension, ST-MBPS has a direct relation with aortic stiffness, which is mediated by an increased ARV. The adverse effects of MBPS may be partly explained by its link with arterial stiffness, mediated by short-term SBP variability.